Effectiveness of Sanitation Treatment for Natural Bloodworms (Tubifex sp.) in Breeding Siamese Catfish (Pangasius hypophthalmus) - Umidayati, Umidayati; Sofia, Iftita Khoirini; Rahardjo, Sinung; Marlina, Erni; Sumiarsih, Sumiarsih; Muktar, Muktar; Aulia, Deni; Indrayati, Artin; Khaerudin, Khaerudin; Sabariyah, Nunung (Journal of Fish Health, 2024)
The demand for Siamese catfish seeds continues to increase every year. Therefore, it is essential to maintain high-quality seeds in adequate quantities, supported by the availability of natural feed such as bloodworms (Tubifex sp.). One of the efforts to improve hygiene and reduce pathogenic bacteria is through the sanitation treatment of feed using fermented tofu waste and mustard greens waste. The fermentation of tofu waste and mustard greens has a high protein content, which can enhance the nutritional value essential for the growth of fish seeds. The objective of this research is to analyze the effectiveness of using hygienic bloodworms treated with fermented tofu waste and mustard greens waste on the performance of Siamese catfish seed breeding. The method employed is a Completely Randomized Design (CRD) with four treatments and three replications. The research data were analyzed using ANOVA statistical tests and Tukey's post-hoc test at a 5% significance level. The sanitation treatment of feed with the addition of fermented tofu waste and mustard greens resulted in the highest nutritional content and the highest abundance of beneficial bacteria on the fifth day of maintenance. The results showed a significant effect () on the absolute growth and specific growth rate of Siamese catfish seeds. The absolute length growth of the Siamese catfish seeds was 9.37±0.044 mm, while the absolute weight growth was 0.08±0.0169 grams. The specific length growth rate of the Siamese catfish seeds was 7.10±0.017%, and the specific weight growth rate was 18.35±0.025%. The survival rate of Siamese catfish seeds across all treatments reached 98%. The sanitation treatment of natural bloodworms with fermented tofu waste and mustard greens is recommended to enhance the nutritional content of bloodworms and accelerate the growth of Siamese catfish seeds.